Dehydrogenative coupling reactions with oxidized guanidino-functionalized aromatic compounds: novel options for σ-bond activation - Wild, Ute; Federle, Stefanie; Wagner, Arne; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2016)
We present a new option for metal-free σ-bond activation, making use of oxidized, guanidino-functionalized aromatic compounds (GFAs). We demonstrate this new option by the homocoupling reactions of thiols and phosphines. The kinetics and the reaction pathway were studied by a number of experiments (including heterocoupling of thiols and phosphines), supported by quantum-chemical computations. Reaction of the oxidized GFA with p-dihydrobenzoquinone to give p-benzoquinone shows that typical proton-coupled electron-transfer reactions are also possible.
Gesehen am 24.08.2020